El riesgo percibido por el trabajador de la construcción: ¿qué rol juega el oficio? - Rodríguez Garzón, Ignacio (2013)
This article presents a study of the perceived risk in the construction sector. The study was conducted from the analysis of questionnaires from several samples of construction workers from southern Spain. We report the perceived risk profile obtained from the psychometric paradigm through qualitative attributes and then we analyze the results. Stands out the attribute regarding how work affects our own long-term health. This represents something new with respect to previous studies. Also analyzed by analysis of variance (ANOVA) the effects of socio-demographic variable craft with respect to the different attributes of the perceived risk of the questionnaire. It presents the differences obtained between the group of masons and framers.